Neurogenic Dysphagia in Subdural Hematoma - Won, Sae-Yeon; Krieger, Simon; Dubinski, Daniel; Gessler, Florian; Behmanesh, Bedjan; Freiman, Thomas M.; Konczalla, Juergen; Seifert, Volker; Lapa, Sriramya (Frontiers in Neurology, 2022)
Introduction: Dysphagia is a common and severe symptom of traumatic brain injury (TBI) affecting up to 78% of patients. It is associated with pneumonia, increased morbidity and mortality. Although subdural hematoma (SDH) accounts for over 50% of TBI, the occurrence of dysphagia in this subtype has not been investigated. Methods: All patients with SDH admitted to the author´s institution between 2007 and 2020 were included in the study. Patients with SDH and clinical suspicion for dysphagia received a clinical swallowing assessment by a speech and language pathologist (SLP). Furthermore, the severity of dysphagia was rated according to the swallowing disorder scale. Functional outcome was evaluated by the Glasgow outcome scale (GOS). Results: Of 545 patients with SDH, 71 patients had dysphagia (13%). The prevalence of dysphagia was significantly lower in the surgical arm compared to the conservative arm (11.8% vs 21.8%; OR 0.23; p=0.02). Independent predictors for dysphagia were GCS <13 at admission (OR 4.17; p<0.001), cardiovascular disease (OR 2.29; p=0.002) and pneumonia (OR 2.88; p=0.002) whereas operation was a protective factor (OR 0.2; p<0.001). In a subgroup analysis, right-sided SDH was an additional predictor for dysphagia (OR 2.7; p<0.001). Overall, patients with dysphagia improved significantly under SLP treatment from the initial diagnosis to hospital discharge (p<0.01). However, a subgroup of patients with the most severe grade of dysphagia showed no significant improvement. Patients with dysphagia had significantly worse outcomes (GOS 1-3) compared to those without dysphagia (48.8% vs 26.4%;p<0.001). Conclusion: Dysphagia is a frequent symptom in SDH and the early identification of dysphagia is crucial regarding initiation of treatment and functional outcome. Surgery is effective in preventing dysphagia and should be considered in high-risked patients.